KONSEP INTERSUBJEKTIVITAS DALAM PHENOMENOLOGY OF SPIRIT KARYA GWF HEGEL - Bito Wikantoso (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2016)
One of the basic concepts of the Hegel’s critic on the modern society which differentiate it from that of the liberalism is the concept of subjectivity. For Hegel, the self-consciousness is constructed of the self-consciousness of others. This study concerns the intersubjectivity comprensively explained within the Hegel’s system of philosophy. Thus, it has made the Hegel’s idea is more outstanding than what the other philosophers of the same period have.